Pengaruh Efisiensi, Literasi Finansial, dan Digital Capability Terhadap Tendensi Penggunaan Digital Payment (E-Wallet) pada Mahasiswa Universitas Qomaruddin Gresik - Lutfi, Lutfi (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2025)
In today's era, technological developments are very beneficial for humans in carrying out their activities. One technology that can make it easier for humans to shop is e-wallet. This research purposes to reveal the partial and simultaneous effects of efficiency, financial literacy, digital capabilities on the tendency to use digital payments (e-wallet) among students of Qomaruddin Gresik University. This study is included in the quantitative type. The technique for sampling used is probability sampling through simple random sampling. Respondents in this research were students of Qomaruddin Gresik University. Data analysis techniques were carried out using multiple linear regression tests, and hypothesis tests (T test and F test). The research results showed that partially the variables of efficiency, financial literacy, digital capabilities have a positive and significant effect on the tendency to use digital payments (e-wallet). Furthermore, simultaneously the variables of efficiency, financial literacy, and digital capabilities simultaneously have a positive and significant effect on the tendency to use digital payments (e-wallet). Based on the results of the determination coefficient test (R2), it is known that efficiency, financial literacy, and digital capability influence the tendency to use digital payments (e-wallets) among students at Qomaruddin Gresik University by 80.5%, while the remaining 19.5% is impacted by other variables not discussed in this research.